Effect of Therapeutic Ultrasound on Calcaneal Tendon Heating and Extensibility in Dogs - Acevedo, Betzaida; Millis, Darryl L.; Levine, David; Guevara, Jose L. (Frontiers in Veterinary Science, 2019)
Objective- To (1) characterize the warming pattern of canine calcaneal tendons during and after four different therapeutic ultrasound (US) treatment protocols, and (2) to quantify changes in tarsal flexion immediately after therapeutic US treatment, and following return to baseline temperature. Design- A prospective, crossover, experimental study Animals- Ten adult hound-type breed dogs Procedure- Therapeutic ultrasound (3.3 MHz) was applied to one calcaneal tendon of anesthetized dogs using four different settings applied in random fashion (1.5 and 1.0 W/cm2 continuous, and 1.5 and 1.0 W/cm2 pulsed US) while the temperature of the tendon was recorded by a thermistor needle. The contralateral tendon was used to compare extensibility of the treated soft tissues by measuring changes in tarsal joint flexion before, immediately after, and 5-minutes after continuous US treatment at 1.5 W/cm2 for 10 minutes. Results- The greatest increase in tendon temperature occurred with continuous US at 1.5 W/cm2. Pulsed US resulted in minimal tendon heating. Most of the increase in tissue temperature occurred within the first three minutes of US application. Tarsal flexion increased significantly following US treatment; however, it returned to near baseline within 5 minutes after US was discontinued. Conclusion and Clinical Relevance- Continuous US of the calcaneal tendon at 1.5 W/cm2 resulted in the greatest increase in tissue temperature while maintaining a safe range of tissue temperature increase. Tendon heating and heat dissipation were slightly different from what has been reported for muscle. Our results suggest that 3.3 MHz US applied to tendon for greater than 3 minutes may not provide additional tissue temperature increase. Therapeutic US resulted in increased tarsal flexion, however, the change was only transitory. Therefore, stretching exercises should be performed during and immediately after US.